Community Structure and Ecological Conditions of Sea Cucumbers (Holothuroidea) in The Coastal Village of Pasokan, Walea Besar District, Central Sulawesi - Ilyas H. Husain; Chairunnisah J. Lamangantjo (Jurnal Biologi Tropis, 2023)
Sea cucumber communities in the wild have different population sizes because there is a high species interaction within the community. Based on the biological organization that is used to express community structure, species diversity is unique to the community level. The objective is to ascertain the structure of sea cucumber communities along the coast of Pasok Village in the Walea Besar District of Central Sulawesi. Data are collected using transect lines, which are divided into three observation stations with ten sampling plots at each. The research method is descriptive-quantitative. The community structure can be known from the domination index (ID), diversity index (H'), and abundance index (J) used to process the data. The results of the study found the diversity index showed the numbers 1.092, 1.056 and 1.089. The dominance of Holothuria scraba species was 0.2 Indv/m2, Holothuria atra 0.14 Indv/m2, and Bohadscia marmorata 0.08 Indv/m2. The highest abundance value belonged to the species Holothuria atra 0.377 Indv/m2 and the lowest to Bohadscia marmorata 0.305 indv/m2. The results showed that the structure of the Holothuroidea community in Pasokan Pantai Village, Walea Besar District, Central Sulawesi, was in the present category.